2013
DOI: 10.1097/mnm.0b013e32835a2eea
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between sarcoidosis and IgG4-related disease by whole-body 67Ga scintigraphy

Abstract: (67)Ga scintigraphy was useful in differentiating between the two diseases. Uptake in mediastinal LNs, in supraclavicular LNs, and in the muscle was specific to sarcoidosis, whereas uptake in the pancreas and in the submandibular gland indicated IgG4-related disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…A study of gallium scanning focused on comparison between sarcoidosis and IgG4 disease showed uptake in different patients at variable sites including mediastinal, hilar, supraclavicular, inguinal, submandibular and paraaortic lymph nodes, lacrimal and parotid glands, lung, heart, spleen, kidney, and pancreas. [12] IgG4-RSD showed uptake at various sites including hilar, paraaortic, and mediastinal lymph nodes, lacrimal, parotid, submandibular glands, lung, pancreas, and kidney. [12] Thus, the 2 entities showed overlapping regions of gallium uptake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of gallium scanning focused on comparison between sarcoidosis and IgG4 disease showed uptake in different patients at variable sites including mediastinal, hilar, supraclavicular, inguinal, submandibular and paraaortic lymph nodes, lacrimal and parotid glands, lung, heart, spleen, kidney, and pancreas. [12] IgG4-RSD showed uptake at various sites including hilar, paraaortic, and mediastinal lymph nodes, lacrimal, parotid, submandibular glands, lung, pancreas, and kidney. [12] Thus, the 2 entities showed overlapping regions of gallium uptake.…”
Section: Discussionmentioning
confidence: 99%
“…[12] IgG4-RSD showed uptake at various sites including hilar, paraaortic, and mediastinal lymph nodes, lacrimal, parotid, submandibular glands, lung, pancreas, and kidney. [12] Thus, the 2 entities showed overlapping regions of gallium uptake. Though in our case pathological studies were not done on all of the gallium-positive lesions, all of the gallium-avid lesions in our case showed complete remission after steroid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Uptake in the bilateral lacrimal glands on scintigraphy, the so-called "panda sign," is characteristic of patients with sarcoidosis 8,9) . Ishii et al 10) have reported a comparison between sarcoidosis and injection alone 6,7) . This patient received combination therapy with systemic steroids and intralesional steroid injection, because he had a prior history of systemic sarcoidosis and certain symptoms such as constriction of the visual field caused by the impairment of eye-opening, and extraocular symptoms including polyarthralgia.…”
Section: Discussionmentioning
confidence: 99%
“…related disease using 67 Ga scintigraphy10) ; abnormal uptake in the lacrimal glands was observed in 96% of patients with sarcoidosis, compared to 62% of patients with IgG 4 -related disease. Uptake in the mediastinal LNs, in the supraclavicular LNs, and in muscle is specific to sarcoidosis, while uptake in the pancreas and submandibular gland indicates IgG 4 -related disease.…”
mentioning
confidence: 95%
“…Las características mencionadas hacen difícil diferenciar estas dos enfermedades, a veces se trata de manera errónea la IgG4, bajo el supuesto diagnóstico de sarcoidosis (68) e incluso hay reportes en la literatura de pancreatitis por IgG4, con compromiso granulomatoso en ganglios mediastinales y pulmón, donde se plantea la coexistencia de ambas (69). Ante esta difícil situación, se ha propuesto la gammagrafía con galio-67 como herramienta útil en el diagnóstico diferencial, mediante la captación en páncreas, glándulas submandibular (especialmente si es asimétrica) en enfermedad por IgG4, mientras en la sarcoidosis este predomina en glándulas lacrimales, adenopatías supraclaviculares, mediastinales y el tejido muscular (70).…”
Section: Diagnóstico Diferencialunclassified